THE INFLUENCE OF BKK INFORMATION SYSTEM SERVICES ON MANPOWER DISTRIBUTION IN VOCATIONAL HIGH SCHOOLS - Fauziah, Syifa; Herawan, Endang; Suryadi, Suryadi (Universitas Pendidikan Indonesia, 2024)
This study examines the impact of a Special Job Exchange (Bursa Kerja Khusus - BKK) information system service on the employment rate of graduates from Al-Manshuriyah Vocational High School (SMK). This research based on the quality of information services as the main influencing indicator overall benefits to workforce distribution institutions such as BKK in vocational schools. Utilizing a quantitative methodology, the study surveyed 162 respondents, including school staff, recent alumni, and current students. Findings revealed a significant positive correlation between the quality of the information system services provided by BKK and the successful job placement of graduates. Statistical analysis using SPSS showed a Pearson correlation coefficient of 0.300, indicating a low yet positive relationship. Additionally, regression analysis confirmed that 5.3% of the variance in job placement success could be attributed to the quality of the information system services. These results underscore the importance of robust information system services in enhancing the operational efficiency of BKK and improving graduate employment outcomes. The study suggests further development and enhancement of these services to attract more company partnerships and diversify job opportunities for graduates.